2022
DOI: 10.1155/2022/8798861
|View full text |Cite
|
Sign up to set email alerts
|

Arbutin Inhibited Heat Stress-Induced Apoptosis and Promoted Proliferation and Migration of Heat-Injured Dermal Fibroblasts and Keratinocytes by Activating PI3K/AKT Signaling Pathway

Abstract: Objective. Studies have shown that arbutin has antioxidant and anti-inflammatory activities, which makes it suitable for treating skin wounds. We designed this study to investigate the effect of arbutin on heat-induced apoptosis, proliferation, and migration of dermal fibroblasts and keratinocytes and to explore the molecular mechanism. Methods. In vitro, HaCAT and dermal fibroblast (DFL) cells were cultured and used to establish a heat stress-injured skin cell model. We investigated the effects of arbutin on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In our results, overlapped DE in cows’ circRNAs under heat stress was most enriched in choline metabolism, which is related to alleviating heat-stress-induced damages by reducing oxidative stress [ 39 ]. Furthermore, PI3K/AKT [ 40 ], sphingolipid [ 36 ] and cAMP [ 37 ] have been proved to be important signaling molecules participating in adaptation to heat stress by affecting multi-level regulatory networks. From our results, the RT and RR significantly increased but the milk yield decreased with the THI in cows ( Table 2 ), which revealed that Holstein cows in Beijing were undergoing severe temperature stress in July.…”
Section: Discussionmentioning
confidence: 99%
“…In our results, overlapped DE in cows’ circRNAs under heat stress was most enriched in choline metabolism, which is related to alleviating heat-stress-induced damages by reducing oxidative stress [ 39 ]. Furthermore, PI3K/AKT [ 40 ], sphingolipid [ 36 ] and cAMP [ 37 ] have been proved to be important signaling molecules participating in adaptation to heat stress by affecting multi-level regulatory networks. From our results, the RT and RR significantly increased but the milk yield decreased with the THI in cows ( Table 2 ), which revealed that Holstein cows in Beijing were undergoing severe temperature stress in July.…”
Section: Discussionmentioning
confidence: 99%